A lack of timing-dependent effects of transcranial direct current stimulation (tDCS) on the performance of a choice reaction time task. (21st June 2022) - Sevilla-Sanchez, Marta; Hortobágyi, Tibor; Carballeira, Eduardo; Fogelson, Noa; Fernandez-del-Olmo, Miguel
Highlights: Anodal transcranial direct current stimulation failed to improve motor retention. All participants improved motor performance up to 24 h after the intervention. tDCS effects over M1 seem to be different for serial versus choice RT tasks. Abstract: Anodal transcranial direct current stimulation (tDCS) can enhance the retention of a previously practiced motor skill. However, the effects of tDCS on the performance of the choice reaction time task are not fully understood. We examined the effects of anodal tDCS over the left primary motor cortex (M1) on the retention of a 4-choice visual-motor reaction time task (4-ChRT). Right-handed healthy participants (n = 100) were randomly assigned to five groups: three groups received anodal tDCS: before (tDCSbefore ), during (tDCSduring ), or after (tDCSafter ) motor practice. In addition, there were two control groups: with (CONmp ) and without (CON) motor practice. We evaluated the speed and precision of the 4-ChRT task before (PRE), during, and 24 h (POST) after the interventions. All groups, including the non-stimulation (CONmp ) and non-practice groups (CON), improved (p < 0.05) motor retention (Δ4-ChRT: 35.8 ± 36.0 ms). These findings suggest that the tDCS effects over M1 may differ for serial versus choice RT tasks, perhaps due to the different brain areas involved in each motor task.